The physical and technical characteristics of English language teaching courseware in Malaysia - Mukundan, Jayakaran; Hossein, Vahid Nimehchisalem; Sayadian, Sima (Canadian Center of Science and Education, 2012)
The present paper reports the findings of a study that investigated the physical and technical characteristics of the English language teaching courseware in Malaysia. A randomly selected group of English language teachers in Malaysia (n=200) were surveyed to evaluate the courseware. SPSS (18.0) was applied to analyze the data. The results showed that the teachers consider the technical and physical characteristics of the courseware (its technological sophistication and user-friendliness among others) to be of a moderate level. The findings can be useful for educational software developers as well as English language teachers and researchers. More research is needed to find how teachers evaluate the courseware in reference to its pedagogical appropriateness and learner attributes.